PENGARUH INFORMASI LABA TERHADAP REAKSI PASAR DENGAN MANAJEMEN LABA RIIL DAN MANAJEMEN LABA AKRUAL SEBAGAI VARIABEL MODERASI - Santi Santi; Kurniawati Kurniawati (Universitas Katolik Indonesia Atma Jaya, 2019)
This study aims to investigate the effect of earnings information on market reaction with accrual and real earnings management as the moderating variables. The sample of this study is manufacturing companies listed in the Indonesia Stock Exchange in 2012-2015. Samples are collected by purposive sampling and resulted in 58 companies as the final sample. Data were analyzed using Moderated Regression Analysis (MRA) for testing hypothesis with significance level 5%. The statistical tool used is SPSS 22.The results of this study shown that market reacts positively significant toward earnings management and real earnings management in aggregate weaken the effect of earnings information toward market reaction. Real earnings management through discretionary expenses strengthen the effect of earnings information toward market reaction. Meanwhile, real earnings management through sales manipulation and overproduction, and accrual earnings management do not moderate the effect of earnings information toward market reaction.